PERAN CIA TRIAD, PRIVASI, DAN TERMS AND CONDITIONS DALAM KEPERCAYAAN DIGITAL SISTEM INFORMASI - Evy Nurmiati; Ghein Karimah (SULIWA: Jurnal Multidisiplin Teknik, Sains, Pendidikan dan Teknologi, 2026)
Rapid advancements in information technology have increased the use of digital systems across various sectors, including business, education, and government. While information systems offer convenience in data management and operational efficiency, they also introduce new risks related to information security and data protection. This condition highlights that digital systems must not only be efficient but also capable of ensuring security and building user trust. This study aims to analyze the role of confidentiality, integrity, and availability as fundamental principles of information security, along with privacy and Terms and Conditions, in establishing digital trust within modern information systems. A qualitative approach was employed using a literature review method, where data were collected from relevant scientific journals and analyzed descriptively and analytically to identify relationships among key concepts. The findings indicate that security principles provide a strong technical foundation but are not sufficient to address challenges related to human behavior. Privacy plays a crucial role in protecting users’ personal data, while Terms and Conditions contribute to transparency in digital service management. The integration of these aspects demonstrates a strong interconnection in building digital trust. This study emphasizes the importance of a comprehensive approach to enhancing user trust and provides insights for improving the reliability of digital systems in organizational contexts.